Testing of symmetric biphasic stimulation in Vim-DBS ET patients: a randomized-controlled pilot study - Boogers, Alexandra; Peeters, Jana; Van Bogaert, Tine; De Vloo, Philippe; Vandenberghe, Wim P.; Nuttin, Bart; Mc Laughlin, Myles (Frontiers in Neurology, 2024)
Introduction Symmetric biphasic pulses have been shown to increase the therapeutic window compared to standard cathodic pulses in ET Vim-DBS patients. Furthermore, three hours of stimulation with biphasic pulses caused less stimulation-induced ataxia compared to cathodic pulses. Therefore, an investigation of the longer-term safety of biphasic pulses is warranted. Methods Seven ET patients were included in a randomized double-blind, cross-over design of one week home-use of symmetric biphasic stimulation (anodic phase first) versus cathodic stimulation. Amplitude was set in a double-blinded way, at the tremor arrest threshold. The primary outcome was safety assessed by documenting the adverse events. Secondary outcome parameters were stimulation amplitude, tremor (Fahn-Tolosa-Marin Tremor Rating Scale) and ataxia (International Cooperative Ataxia Rating Scale) severity, quality of life (Quality of Life in Essential Tremor Questionnaire) and cognition (Montreal Cognitive Assessment). Three patients continued in the open-label extension phase for 3 months, during which biphasic stimulation-only was further assessed by the same outcome parameters. Results During the 1 week testing, no adverse effects were reported. To obtain equivalent tremor control, the amplitude of the biphasic pulse was significantly higher compared to that of the cathodic pulse (p = 0.003). The other outcome parameters were not significantly different. During the open-label study, one patient used the remote control to increase the amplitude, leading to two falls caused by stimulation-induced ataxia. No other adverse effects occurred. Discussion and conclusion In a small cohort, when tested for one week, symmetric biphasic pulses suggest to be safe, but require higher stimulation amplitudes. Further follow-up studies are needed to investigate long-term effects and safety.